Dr. H.M. Amien Rais, demi pendidikan politik, saya siap jadi calon presiden - Hasyim, Mustofa W.; Alwustho, Mathori; Effendi, Lutfi (Yogyakarta : Titian Ilahi Press, 1997)
On Amien Rais, b. 1944, the chairman of Muhammadiyah, an Islamic organization in Indonesia and issues on his candidacy for president, 1998-2003
'Penyusun, Mustofa W. Hasyim, Mathori Alwustho, Lutfi Effendi'--T.p. verso
Includes index
Keywords: Rais, M. Amien; Indonesia -- Politics and government -- 1966-1998